Answer:
1) (1, -2) -------->Last option
2) (-3/4 , -1/5) -------> First option
Explanation:
1)
8x + 2y = 4 (1)
-4x + 3y = -10 (2)
Multiply equation(2) by 2
2(-4x + 3y) = 2(-10)
-8x + 6y = -20
So now you have
8x + 2y = 4
-8x + 6y = -20
------------------------add
8y = -16
y = -2
Substitute y = -2 into 8x + 2y = 4
8x + 2(-2) = 4
8x - 4 = 4
8x = 8
x = 1
Solution (1 , -2)
2)
8g - 5h = 7 (1)
4g + 10h = 1 (2)
Multiply equation(2) by -2
-2(4g + 10h) = -2(1)
-8g - 20h = -2
Now you have 2 equations
8g - 5h = 7
-8g - 20h = -2
----------------add
-25h = 5
h = -1/5
Substitute h = -1/5 into 8g - 5h = 7
8g - 5(-1/5) = 7
8g + 1 = 7
8g = -6
g = -3/4
Solution (-3/4 , -1/5)